Institutional change in social-ecological systems: The evolution of grassland management in Inner Mongolia. (November 2017) - Robinson, Brian E.; Li, Ping; Hou, Xiangyang
Highlights: Communities in Inner Mongolia experienced dramatic change over the past millennium. The social-ecological systems (SES) framework often assesses institutional stability. Here we relate changes in SESs to changes in outcomes in grassland systems. Formerly tightly coupled SES have been decoupled by markets and technology. Currently, the complex policy environment induces tenure insecurity for herders. Abstract: Communities living in the grasslands of present day Inner Mongolia have experienced dramatic social, economic and ecological changes over the past millennium. More recently, these grasslands have undergone widespread degradation, raising concern for securing local herders' livelihoods. To understand these changes in ecological and welfare outcomes over long time scales, we define five broad periods of relative institutional stability over the past millennium, characterize social-ecological system during each period, and then assess major changes between these periods. Looking at changes in institutional contexts helps explain some of our outcomes of interest. We find that while much attention has been given to the change in grassland lease structures in China, the role of market integration and buffers against historically natural constraints on livestock production (e.g., protection from the winter months) have decoupled formerly tight local social-ecological links. This decoupling, along with weak land tenure security due to a complex and volatile policy landscape, suppresses local incentives for grassland conservation.